Evaluation of pedestrian navigation in Smart Cities. (July 2021) - Stähli, Lisa; Giannopoulos, Ioannis; Raubal, Martin
This work addresses recent research in the area of pedestrian navigation aids that aims at finding alternatives to the widely used map-based turn-by-turn navigation systems in the context of Smart City environments. Four different approaches of pedestrian navigation systems were compared to each other in a user experiment that was conducted in a virtual environment: (1) map-based, (2) landmark-based, (3) augmented reality, and (4) public display navigation. The results of the experiment with 45 participants conducted in a virtual environment suggest that the augmented reality navigation performs best concerning efficiency and effectiveness and the landmark-based navigation performs worst in the context of Smart Cities.